Depth-Related Curing Potential of Ormocer- and Dimethacrylate-Based Bulk-Fill Composites - Ramona S. Oltramare (MDPI AG, 2021)
The aim of this in vitro study was to investigate the degree of C=C double bond conversion of high-viscosity dimethacrylate- or ormocer-based bulk-fill composites as a function of measurement depth. Four bulk-fill composites (Tetric EvoCeram Bulk Fill, x-tra fil, SonicFill, and Bulk Ormocer) and the conventional nanohybrid composite Tetric EvoCeram were applied in standardized Class II cavities (n = 6 per group) and photoactivated for 20 s at 1350 mW/cm2. The degree of conversion of the composites was assessed using Fourier-transform infrared spectroscopy at seven measurement depths (0.15, 1, 2, 3, 4, 5, 6 mm). Data were analyzed using repeated measures ANOVA and one-way ANOVA with Bonferroni post-hoc tests (α = 0.05). The investigated bulk-fill composites showed at least 80% of their maximum degree of conversion (80% DCmax) up to a measuring depth of at least 4 mm. Tetric EvoCeram Bulk Fill and Bulk Ormocer achieved more than 80% DCmax up to a measuring depth of 5 mm, x-tra fil up to 6 mm. The conventional nanohybrid composite Tetric EvoCeram achieved more than 80% DCmax up to 3 mm. In contrast to the conventional composite, the investigated ormocer- and dimethacrylate-based bulk-fill composites can be photo-polymerized in thick layers of up to at least 4 mm with regard to their degree of C=C double bond conversion.